MENINGKATKAN SELF-ESTEEM SISWA MELALUI TEKNIK ASERTIF TRAINING PADA SISWA KELAS XI TMO 1 SMK NEGERI 7 SEMARANG - Windaniati, Windaniati (Universitas Negeri Semarang, 2013)
SMK Negeri 7 Semarang is a Technology and Industry Vocational School and is one of favourite vocational schools. Various backgrounds and abilities of students cause various levels of self-esteem possession. Based on the spread psychological scales, there were about 25% (12 of 36) of students of Class XI TMO 1 had self-esteem with low and less categories. This research was aimed to know (1). the effectivity of the training assertive technique in improving the self-esteem of students of Class XI TMO 1 SMK Negeri 7 Semarang; (2). the level of students’ self-esteem improvement through Assertive Training Technique for Students of Class XI TMO 1 SMK Negeri 7 Semarang. This is a counselling guidance action reearch. The subjects were 8 students of Class XI TMO 1. The hypothesis was that through Assertive Training Technique, the self-esteem of students of Class XI TMO 1 could be improved. Data were collected using observations, psychological scales, and interviews. The quantitative dan qualitative data were analyzed descriptively and comparatively, by comparing the conditions in precycle, cycle 1, and cycle 2. The result showed that (1) good self-esteem indicator increased from 23.75% in cycle 1 to 68.75 in cycle 2, or 45%, subjects with enough category decreased from 70% to 31.5%, whereas subjects with less category in cycle 1 (6.25%) did not appear in cycle 2 (0%); (2) high category increased from 0% in cycle 1 to 37.5% in cycle 2, medium category increased form 0% in precycle to 70% in cycle 1 but it decreased to 62.5 in cycle 2. The subjects in the less category in precycle were 87.5, in cycle 1 they decreased to 12.5% and they became 0% in cycle 2. The subjects in low category were 12.5%, no changes in cycle 1, but in cycle 1 they became 0%; (3). Students’ self-esteem, in average, increased 14,32% from the early condition to cycle 1. From cycle 1 to cycle 2, students’ self-esteem increased 14.96%. It was proven that Assertive Training Technique could increase students’ self-esteem (31.42%). Thus, generally this technique was good to be implemented for a big number of students.